Covalent organic framework based multifunctional self-sanitizing face masks. Issue 7 (13th January 2022) - Ding, Luo-Gang; Wang, Song; Yao, Bing-Jian; Wu, Wen-Xiu; Kan, Jing-Lan; Liu, Yueyue; Wu, Jiaqiang; Dong, Yu-Bin
Abstract : A COF-based multifunctional reusable face mask, which exhibits solar-powered self-sanitizing ability with excellent antibacterial and antiviral performance via a triple-modal synergistic treatment, is reported. Abstract : As important personal protective equipment (PPE), face masks play a key role in self-protection during disastrous pandemics caused by the COVID-19 virus and other respiratory viruses. On the other hand, the massive utilization of disposable face masks creates big challenges not only in recycling and sterilizing the used face masks, but also in terms of plastic pollution and resource-saving. So, the development of self-sanitizing reusable face masks is highly imperative. We report herein a covalent organic framework (COF)-based face mask. In this regard, a Ag NP loaded and quinolinecarboxylic acid-linked nanoscale porphyrin COF composite of Ag@DhaTph-COOH is constructed by a three-component one-pot in situ Doebner reaction and sequential solution impregnation and NaBH4 reduction. After mixing the hydroxyl-enriched COF NPs with isocyanate-terminated polyurethane oligomers, the obtained covalently cross-linked COF-dispersion is sprayed onto the outer layer of the non-woven PET fabric surface to yield a face mask with the deposited Ag@DhaTph-COOH NPs. Our face mask is reusable and exhibits solar-powered self-sanitizing ability with excellent antibacterial and antiviral performance via a triple-modal chemo/PDT/PTT synergistic treatment under natural sunlight irradiation.